Affections and teacher training: Principles for inclusive practices of human diversity - Santos, Martha Daniele; Pereira, Daniane; Antunes, Joeli Teixeira (The ESPecialist, 2024)
The aim of this paper is to address selective affect in educational relationships as a probable cause of social inequality through exclusion and school dropout. It is of paramount importance to discuss the relations of omission and naturalization of exclusionary practices in the school routine, from the perspective of a selective affectivity that can cause the invisibilization and school dropout of students with disabilities and/or situations of social vulnerability. The study analyzes the absence of affectivity as one of the possible causes for school dropout. Thus, historically, politically and culturally established power relations are addressed as a form of segregation and social exclusion within the school context and teacher training as a potential vehicle for transgressing ideologies of social inequalities. The research reflects on how the identities of students who go through situations of invisibilization in school institutions are affected, against the backdrop of the process of welcoming these students. This is a theoretical research of bibliographic character and the applied methodology consisted of reading articles on the subject, articulating with the observations made in school and non-school spaces. This research dialogues with the theories of Piaget (1978), Vygotsky (1988, 1993, 1995), Wallon (1971, 2007, 2008) and Freire (1992, 1995, 1996, 2015), understanding that the affective bonds established between educators and students favor the integral development of students with and without disabilities and contribute to the learning process occurring satisfactorily.